Wireless monitoring of cardiac activity: a critical review - Fariborzi, H.; Moghavvemi, M. (Inderscience Publishers, 2009)
Despite significant progress and improvement made in its prevention and treatment, Cardiovascular Disease (CVD) remains to be the main cause of mortality and morbidity in the industrialised world. Patients with the risk of acute heart problems need precise and continuous monitoring. Remote monitoring of patients' heart activity enables the healthcare providers to access the crucial data in real time and help the patients to benefit from mobility in the hospital, home or workplace. This paper critically reviews the current trends and significant challenges in this area and suggests the next steps toward upgrading the ubiquitous healthcare.